Data-driven approach to solve vertical drain under time-dependent loading - Nghia-Nguyen, Trong; Kikumoto, Mamoru; Khatir, Samir; Chaiyaput, Salisa; Nguyen-Xuan, H.; Cuong-Le, Thanh (My University, 2021)
Currently, the vertical drain consolidation problem is solved by numerous analytical solutions, such as time-dependent solutions and linear or parabolic radial drainage in the smear zone, and no artificial intelligence (AI) approach has been applied. Thus, in this study, a new hybrid model based on deep neural networks (DNNs), particle swarm optimization (PSO), and genetic algorithms (GAs) is proposed to solve this problem. The DNN can effectively simulate any sophisticated equation, and the PSO and GA can optimize the selected DNN and improve the performance of the prediction model. In the present study, analytical solutions to vertical drains in the literature are incorporated into the DNN—PSO and DNN—GA prediction models with three different radial drainage patterns in the smear zone under time-dependent loading. The verification performed with analytical solutions and measurements from three full-scale embankment tests revealed promising applications of the proposed approach.
Keywords: artificial neural network; deep learning network; genetic algorithm; particle swarm optimization; time-dependent loading; vertical drain